A pharmacological mouse model suggests a novel risk pathway for postpartum psychosis. (December 2016) - Humby, Trevor; Cross, Ellen S.; Messer, Lauren; Guerrero, Silvia; Davies, William
Highlights: Postpartum psychosis (PP) is a severe psychiatric disorder of unknown cause. Steroid sulfatase (STS) deficiency may influence PP risk. Postpartum inhibition of STS in mice results in behavioural and genetic abnormalities. These abnormalities can be alleviated with an antipsychotic drug. The study suggests a new mouse model and a biological risk pathway for PP. Abstract: Postpartum psychosis (PP) is a severe psychiatric disorder affecting a small proportion of new mothers shortly after childbirth. The molecular pathophysiology underlying the disorder is currently poorly understood, and there are no amenable animal models for the condition; maternal deficiency for the enzyme steroid sulfatase has been proposed as a potential risk mechanism. Here we show that inhibition of steroid sulfatase with 667-COUMATE (10 mg/kg p.o.) in new mouse mothers results in behavioural abnormalities that can be partially alleviated by the administration of the clinically-efficacious antipsychotic ziprasidone (0.3–1.0 mg/kg i.p.). The pattern of behavioural abnormalities in 667-COUMATE-treated mice implicated a genetic substrate at 21–23 cM on chromosome 15; of the 17 genes within this chromosomal interval, only one ( Nov / Ccn3 ) was significantly differentially expressed in the brains of vehicle and 667-COUMATE-treated mice. Two additional members of the Ccn family ( Ccn2 / Ctgf and Ccn4 / Wisp1 ) were also significantly differentially expressed between the two groups, as were three further genes co-expressed with Nov/Ccn3 in brain ( Arhgdig ) or previously implicated in disorder risk by clinical studies ( Adcy8 and Ccl2 ). The expression of Nov / Ccn3, but not of the other differentially-expressed genes, could be normalised by ziprasidone administration (1.0 mg/kg). NOV / CCN3 lies directly under a linkage peak for PP risk at 8q24, and the associated protein possesses numerous characteristics that make it an excellent candidate mediator of PP risk. Our data suggest the 667-COUMATE-treated mouse as a model for PP with some degree of face, construct, and predictive validity, and implicate a novel, and biologically-plausible, molecular risk pathway for PP.